Conflict management and territorial competition seen from public management - Pinella Odar, Marianella (2020)
Understanding that the problematic of the district limits generates the weakening of collection in property tax, main municipal tax administered by the municipalities according to the Organic Law of municipalities. This is the specific case of the border conflict between the districts of Magdalena del Mar and San Isidro, a situation that has long been the case, and affects the social and economic aspect of the populations and residents, limiting the execution of public works and municipal services such as citizen security in the affected districts. Attempts to solve the conflict by the State only polarize the citizens of both communes and stop living in harmony as if they were bordering countries. The study auscultates the negative axes and how the lack of a public policy management tool increasingly sharpens a political situation and respect for the rule of law, where the authorities involved must submit to a technical decision-making body as is the specific case of the National Geographical Institute, which, by means of geographical coordinates, can delimit the territories in conflict. Codice (JEL): Conflict management (D74), interjurisdictional differentials (H73), public economy (H80).